The moderator effect of sex on attitude toward communication, emotional intelligence, and empathy in the nursing field - María del Carmen Giménez-Espert; Vicente-Javier (Universidade de São Paulo, 2017)
ABSTRACT Objectives: to analyze differences in the variables for the object of this study (attitude toward communication, emotional intelligence, and empathy) according to sex; verify correlations among variables between men and women and analyze regression models according to sex. Method: the ATC was used to measure attitudes toward communication; the Jefferson Scale of Empathy was used to measure empathy; and the Trait Meta Mood Scale 24 was used to measure emotional intelligence. The sample was composed of 450 nurses working in 7 hospitals located in Valencia, Spain. The t-test for independent samples was used to verify whether there were statistically significant differences, together with a prior application of the Levene test to assess the equality of variances. The correlations were analyzed using Person's coefficient. Finally, the Beta coefficients of variables predicting ATC's dimensions were verified using hierarchical multiple linear regression according to sex. Results: There are statistically significant differences based on sex for the variables, correlations and power of prediction. Conclusions: This study presents evidence on how the levels of variables (attitudes toward communication, EI, and empathy) vary among nurses according to sex, as well as the relationships established among such variables.